Crossing The Border With Hashtags: Twitter's Bridging The Gezi Park And The Yellow Vest Movements - Seher Karataş; Enderhan Karakoç (Yeni Medya, 2024)
Social movements are a manifestation of societal unrest, from the past to the present. Thanks to the developing technologies over time, there are some changes in the forms of organisation, tools and protests of social movements. Social movements, which are shaped by the penetration of the Internet and social media into lives, keep pace with the age and redefine the scope of the virtual public sphere under the umbrella of new social movements.This article reveals that new social movements, shaped by the infiltration of social media, redefine the virtual public sphere. It analyses the effect of hashtags on the Yellow Vests Movement and the Gezi Park Protest through content analysis with the help of data collected using Twitter Python Library. As a sample, 52 thousand 651 tweets about the Yellow Vests Movement from 17 November 2018 to the end of 2022 are reached and 14 thousand 244 tweets are included in the study, while 13 thousand 003 tweets are included from 100 thousand 550 tweets between 27 May 2013 and 2 July 2013 about the Gezi Park Protest. As a result of the study, it is revealed that the key to new social movements is social media and the teeth of the key are hashtags. However, when the Twitter data set analysed in the study is taken into consideration, it is found that Twitter played an important role in the Yellow Vests and Gezi Park Protests, as well as drawing a route for activists and being one of the platforms used in the movements thanks to its immediacy feature